Late nineteenth-century popular printed poetry in Chile and its contribution to a radical cultural theory. - Sáez, Chiara; Vera, Antonieta (Journal of Iberian & Latin American Studies, 2023)
The subject of this study is Lira Popular in Chile, printed and distributed between 1866 and 1930. It was a publication halfway between literature and journalism, constituting a differentiated and autonomous communicational practice that can be considered a primary source through which to know the world visions and representations of the popular sectors in Chile at the turn of the century, beyond distinction worker – massive. The majority research in this area is one-dimensional studies conducted in response to questions the researchers themselves have prioritized. Instead, the question driving this study is: how to access the content of popular printed poetry in a way in which subjects, topics, and the inherent hierarchical relationships emerge from the very own sources? Through a content analysis, the main finding is an internal consistency on concerns and topics in the works of different poets, showing persons of popular origins acting and thinking politically, both within and outside the modern enlightenment, used as a guide to the concept of absent popular culture. The conclusions aim to the manner in which these findings can contribute to a theory popular culture and their subjects in the context of modern Latin America